Indicazioni e limiti dell’apparecchio gessato in traumatologia pediatrica - Donati, F.; Pagnotta, G. (Lo Scalpello - Journal, 2018)
INDICATIONS AND LIMITS OF PLASTER CAST APPLICATIONS IN PAEDIATRIC TRAUMATOLOGY Surgical indications for the treatment of fractures in children have become increasingly frequent in the latest years, even though plaster cast treatment is still a very common therapeutic option. Various types of plaster casts are known, with different possible applications. Conservative treatment is indicated when the fracture is properly reduced and stable and in younger patients, although there are several other variables to be considered. Plaster cast treatment, with the correct indications, guarantees good results with a low percentage of complications and must therefore be at the base of the clinical practice in paediatric traumatology.